Liver transplantation for the treatment of neuroendocrine liver metastases - Orozco, Gabriel; Ramaiah, Dharani; Cracco, Alejandro; Desai, Siddharth; Gedaly, Roberto (Frontiers in Surgery, 2025)
Neuroendocrine liver metastases (NELM) are commonly observed in patients with advanced neuroendocrine tumors (NETs) and are associated with poor prognosis, primarily due to liver failure and hormone-related complications. While hepatic resection remains the standard surgical approach, orthotopic liver transplantation (OLT) has emerged as a potentially curative treatment in selected patients with unresectable disease. This review summarizes current evidence on the role of OLT in managing NELM, with a focus on patient selection criteria and existing clinical guidelines. Appropriate selection is essential, as improved long-term survival has been consistently demonstrated in patients who meet established eligibility parameters. In conclusion, OLT offers meaningful survival benefits for carefully selected patients with NELM. A multidisciplinary approach and ongoing research into prognostic markers and adjunctive therapies are critical to optimizing outcomes in this challenging clinical setting.